Simultaneous Preparation of Funds and Cash Flow Statements. - Corcoran, A. Wayne (The Accounting Review, 1965)
The article presents a worksheet related to preparation of funds and cash flow statements. In preparing funds and cash flow statements it is customary for accountants to employ two separate worksheets–one for the funds statement and a second for the cash flow statement. The worksheet described in this article eliminates unnecessary duplication of effort by combining both funds and cash flow worksheets. The purpose of the combined worksheet is to facilitate simultaneous preparation of the statement of sources and applications of funds and the statement of cash flow. The initial two columns of the combined worksheet contain measures of changes in the balances of each asset and equity account that have occurred during the period in question. The acquisition of assets with expected useful lives exceeding one year are displayed separately on the cash flow statement. The acquisition of assets with expected lives of less than one year are shown on the cash basis profit and loss statement. A variety of statements may be prepared from the combined worksheet.